Pemasaran Berbasis Data: Cara Memanfaatkan Analitik Untuk Menjangkau Audiens Yang Tepat - Fanisa Amanda; Hendra Riofita (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2024)
the midst of the rapid development of digital technology, data-based marketing has become an essential strategy for companies to increase the effectiveness of their marketing campaigns. This article reviews how analytics can be leveraged to understand audience behavior and preferences, and how this information can be used to target the right consumers with more relevant messages. By using sophisticated analytical tools, companies can extract insights from customer data, from purchasing patterns to interactions with digital platforms, enabling more informed and accurate decision making. This article also discusses various market segmentation techniques and content personalization based on analytical data, and shows how implementing data-driven marketing strategies can increase conversions and customer loyalty. Through this study, the author aims to provide insight into the importance of applying analytics in designing marketing campaigns that are more targeted, efficient and profitable.